2021
DOI: 10.1039/d1ra02061g
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between spectroscopic constants of diatomic molecules: a machine learning approach

Abstract: Through a machine learning approach, we show that the equilibrium distance, harmonic vibrational frequency and the binding energy of diatomic molecules are universally related, independently of the nature of the bond of a molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…For all the nine implemented models, we permute the groups and periods in D train in the training and validation stage and in D tv in the testing stage to impose permutational invariance. 26 That is, the models should not differentiate between x = (p 1 , g 1 , p 2 , g 2 ,.) and x ′ = (p 2 , g 2 , p 1 , g 1 ,.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For all the nine implemented models, we permute the groups and periods in D train in the training and validation stage and in D tv in the testing stage to impose permutational invariance. 26 That is, the models should not differentiate between x = (p 1 , g 1 , p 2 , g 2 ,.) and x ′ = (p 2 , g 2 , p 1 , g 1 ,.)…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Sutherland found that by taking A ′ as a function of groups and periods, better results can be obtained. 19,41 Thanks to machine learning (ML) techniques and the development of extensive spectroscopic databases, 49 it has been possible to study the relationship between spectroscopic constants from a heuristic perspective, i.e., from a data-driven approach, 26 nd optimal potentials based on spectroscopy data 50 and to improve ab initio potentials to match experimental observations. 51 In particular, Gaussian process regression (GPR) models have been used on a large dataset of 256 heteronuclear diatomic molecules.…”
Section: Digital Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Gradient boosting regression has been successfully applied to predict BHs in Diels–Alder reactions, and the reactivity of transition metal complexes . Similarly, GP has shown a great performance in complex potential energy surface fittings, predicting spectroscopic constants of diatomic molecules , and second virial coefficients of organic and inorganic compounds . The selected SQM model was PM7, which is overall the most accurate method implemented in MOPAC2016 .…”
Section: Introductionmentioning
confidence: 99%